2018
DOI: 10.1186/s12885-018-4637-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between circulating tumour DNA and metabolic tumour burden in metastatic melanoma patients

Abstract: BackgroundCirculating tumour DNA (ctDNA) may serve as a measure of tumour burden and a useful tool for non-invasive monitoring of cancer. However, ctDNA is not always detectable in patients at time of diagnosis of metastatic disease. Therefore, there is a need to understand the correlation between ctDNA levels and the patients’ overall metabolic tumour burden (MTB).MethodsThirty-two treatment naïve metastatic melanoma patients were included in the study. MTB and metabolic tumour volume (MTV) was measured by 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 37 publications
(24 reference statements)
5
86
1
1
Order By: Relevance
“…We detected plasma ctDNA in seven of seventeen patients who had at least one somatic mutation in tumor tissue. This is in agreement with three other similar studies using ddPCR, which indicated that ctDNA detection rates are associated with tumor burden 18 , 23 , 43 . McEvoy et al 18 demonstrated a detection rate of 71.8% in a cohort of 32 stage IV patients.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We detected plasma ctDNA in seven of seventeen patients who had at least one somatic mutation in tumor tissue. This is in agreement with three other similar studies using ddPCR, which indicated that ctDNA detection rates are associated with tumor burden 18 , 23 , 43 . McEvoy et al 18 demonstrated a detection rate of 71.8% in a cohort of 32 stage IV patients.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with three other similar studies using ddPCR, which indicated that ctDNA detection rates are associated with tumor burden 18 , 23 , 43 . McEvoy et al 18 demonstrated a detection rate of 71.8% in a cohort of 32 stage IV patients. In keeping with the relationship to burden, detection rates fell to 12% in lower stage patients (EC II and III) 23 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…47,48 For example, in patients with melanoma, ctDNA levels were correlated with metabolic disease volume, estimated with 18 F-labelled fluorodeoxyglucose positron emission tomography. 49,50 Therefore, the ctDNA level was a complex reflection of tumor biology, rather than simply associated with tumor burden or the number of dying cells. This finding suggested that ctDNA measurements might be more relevant to advanced stages of the disease and less relevant to precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%